Jom solat / Nur Liyana Ruslan and Norarifah Ali - Ruslan, Nur Liyana; Ali, Norarifah (Faculty of Art and Design, 2021)
Nowadays, we are currently affected by the dangerous Covid-19 virus. This covid-19 virus is getting widespread in Malaysia because people don’t care about this virus. In this respect, many people have wanted to invent a product that can be used to reduce the spread of the virus. In comparison, products that preserve social distance are often created to make people safer in the public. JomSolat is a product of social distancing while praying in the mosques and suraus to ensure that the community adheres to the SOP of the Mosque by establishing a social distance. This product can be used during the pandemic while at mosque and surau. This product is for people who visit the mosque and surau who want to pray more peacefully and comfortably. This product works very well because it makes people be more vigilant about social distance between them, especially for people who often go to mosques and surau during Friday’s prayers in large numbers. This product has allowed people to pray more peacefully and comfortably in the mosque and surau. Moreover this product for social distance has several types produced for certain locations or particular sites, such as public areas, public transportation or shopping malls.